Influence of physical training on the function of autonomic nervous system in professional swimmers - Palak, K.; Furgala, A.; Biel, P.; Szygula, Z.; Thor, P. j. (Medicina Sportiva, 2013)
Introduction: Regular endurance - type physical exercise exerts positive effect on the capacity and endurance of body and the activity of the autonomic nervous system (ANS). In contrast, the exercise load used in professional sport may lead to significant functional impairment of all tissues and organs, including ANS. These changes can lead to overtraining phenomenon. Objective: To analyze the influence of prolonged - intense, single - moderate, and single - intense physical exercise on the function of ANS in the training group of swimmers. Methods: The study included 10 healthy swimmers and 31 healthy volunteers as the control group. The activity of ANS was evaluated on the basis of the temporal and frequency indices of heart rate variability (HRV): mRR, SDNN, pNN50, rMSSD, TP, LF, HF, and LF/HF. The measurements were taken twice: during the preparatory (January 2012) and competition (May 2012) phases of the yearly training cycle, prior to and after the training. Results: Compared to respective pre-training values, a significant decrease in HRV indices: SDNN (P < 0.015) and pNN50 (P < 0.047), was documented after the training session conducted during the preparatory phase. In contrast, a decrease in mRR (P < 0.013) and pNN50 (P < 0.028) was observed during the competition phase. We did not observe significant differences in values of frequency HRV indices determined during the preparatory phase and following four months of training, i.e. during the competition phase. Conclusions: No significant changes in various vegetative indices in response to an applied load of swimmers. This suggests that such a high training load is safe and is not associated with the signs of overtraining.